2013
DOI: 10.1098/rsob.130163
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic efferent synaptic transmission regulates the maturation of auditory hair cell ribbon synapses

Abstract: Spontaneous electrical activity generated by developing sensory cells and neurons is crucial for the maturation of neural circuits. The full maturation of mammalian auditory inner hair cells (IHCs) depends on patterns of spontaneous action potentials during a ‘critical period’ of development. The intrinsic spiking activity of IHCs can be modulated by inhibitory input from cholinergic efferent fibres descending from the brainstem, which transiently innervate immature IHCs. However, it remains unknown whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 48 publications
1
51
0
Order By: Relevance
“…), which is abundantly expressed in the cochlea (Johnson et al . ), in auditory brainstem neurons (Moritz et al . ) and also in the calyx of Held (Young & Neher, ; Luo & Sudhof, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), which is abundantly expressed in the cochlea (Johnson et al . ), in auditory brainstem neurons (Moritz et al . ) and also in the calyx of Held (Young & Neher, ; Luo & Sudhof, ).…”
Section: Discussionmentioning
confidence: 99%
“…As a neuropeptide of a very small size, UCN3 is packed into dense core vesicles (van den Pol, 2012) and can then be released by either kiss-and-run or full fusion depending on the form of stimulation (Zhang et al 2011). The sensor of activity levels which decides the mode of vesicle fusion is suggested to be synaptotagmin (Zhang et al 2011), which is abundantly expressed in the cochlea (Johnson et al 2013), in auditory brainstem neurons (Moritz et al 2015) and also in the calyx of Held (Young & Neher, 2009;Luo & Sudhof, 2017). In future studies we will target the physiology of this receptor system in the auditory pathway to reveal the cellular mechanisms underlying the effects of UCN3 on stress recovery described in the present study.…”
Section: Cellular Mechanisms Of Ucn3 Signallingmentioning
confidence: 99%
“…; Johnson et al . b ). Taken together, these mechanisms generate a topographically specific firing pattern necessary for maturation of the synaptic machinery of IHC ribbon synapses before hearing onset (Johnson et al .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this model, activation of acetylcholine receptors in acutely isolated cochleae caused IHCs to switch from sustained to burst firing ( Johnson et al, 2011 ). However, in vivo recordings from auditory brainstem revealed that neuronal burst firing remains, with altered features, in α9 knockout mice ( Clause et al, 2014 ), which lack functional efferent signaling in IHCs ( Johnson et al, 2013 ), and persists in IHCs and auditory neurons in cochleae maintained in vitro without functional efferents ( Johnson et al, 2013 ). Thus, cholinergic efferents appear to modulate the temporal characteristics of bursts, but are not essential to initiate each event.…”
Section: Introductionmentioning
confidence: 99%